Pengaruh Kepuasan Pelanggan dan Hambatan Berpindah TerhadapRetensi Pelanggan Kartu Prabayar SimPATI di Wilayah Semarang - Novianti, Novianti; Suryoko, Sri; Nugroho, Hari Susanto (Jurnal Ilmu Administrasi Bisnis, 2013)
This research was conducted to determine the effect of customer satisfaction and switching barriers on customer retention SimPATI prepaid card in Semarang region. This study used an explanatory approach to research on 100 respondents. Sampling is done by accidental sampling technique. Data analysis techniques used are simple regression and multiple regression. Determination test result showed that 40,7% of customer retention variables can be explained by the variable customer satisfaction, 47,7% customer retention variables can be explained by the variable switching barriers. 58,9% customer retention variables can be explained by the customer satisfaction and switching barriers. The result of hypothesis testing (t test) that customer satisfaction has a positive and significant impact on customer retention. Switching barriers has a positive and significant impact on customer retention. Hypothesis test (F test) the customer ssatisfaction and switching barriers together – each has a positive influence and significant impact on customer retention. So that conclude the two variables, both individually and collectively – each has a positive and significant impact on the customer retention of SimPATI prepaid card in Semarang region.